Ridiculously simple furniture projects : great looking furniture anyone can build - Carlsen, Spike , 1952- (Fresno, California : Linden Publishing, 2011)
Blending the practicality of IKEA with the creativity of Martha Stewart, this collection of innovative projects is presented with simplicity of construction in mind. The suggested pieces are practical, have broad appeal, and carry a high brag factor upon completion. Requiring minimal assembly time and tools, this concise, engaging, and even humorous guide offers countless tips as well as clear and instructive photography. The majority of the projects also incorporate clever construction, such as the use of bifold doors, stock cabinets, and off-the-shelf lumber, guaranteeing that the required materials are both inexpensive and easily accessible. Featuring ideas for furnishing both the interior and the exterior of the home,this handbook is ideal for weekend woodworkers
1. Living room and bedroom -- 2. Home office and media storage -- 3. Kitchen and dining room -- 4. Outdoors
Includes index
Keywords: Furniture making -- Amateurs' manuals